Cervical Stump Cancer after Subtotal Hysterectomy: A Retrospective Research of 127 Cases from China and Literature Review - Jia Wang; Xi Zeng; Lin Min; Lin Li (Clinical and Experimental Obstetrics & Gynecology)
Background: Cervical stump cancer is a rare disease, which is subsequent to a previous subtotal hysterectomy. Among patients who underwent a subtotal hysterectomy, approximately 1%–3% develop cervical stump cancer which represents 3%–9% of all the cervical cancers. Methods: After acquiring consent from our ethics committee, we recruited the subjects and reviewed the patients’ data of those who were admitted to our hospital from January 2010 to December 2022. Written informed consent from all the study participants was acquired, and all materials complied with the Declaration of Helsinki and ethical standards. The patients’ data records, including clinical characteristics, treatment methods, human papillomavirus (HPV) infection conditions before the operation, complications of the treatment and follow-up status were analyzed. The HPV infection status was detected by Tellgen systems (Tellgen Corporation, Shanghai, China). SPSS software (Version 22.0, IBM Company, Armonk, NY, USA) was used for data analysis. Data is shown as mean ± standard deviation. A two-side p value < 0.05 was considered to be significant. Results: There were 127 cases with cervical stump cancer treated in our hospital during this period. The interval time between subtotal hysterectomy and stump cancer was 130.7 months. Vaginal bleeding, postcoital bleeding and pelvic pain were the main symptom. Seventy-two cases were squamous cancer and adenocarcinoma occurred in 39 cases. All patients received surgery or concurrent chemoradiotherapy. One hundred and ten cases were included in the follow-up. The median observation time was 65 months. Vaginal bleeding, gastrointestinal symptoms and vaginal contracture were the most common complications. The median observation time was 65 months and the 5-year disease-free rate for all patients was 51.8% with the 5-year overall survival for all patients being 77.3%. Conclusions: Subtotal hysterectomy results in a potential to develop cervical stump cancer. Cytological studies, cervical biopsy and endocervical curettage should be considered before a subtotal hysterectomy is performed. The patients should be well informed of the risk for retaining the cervical stump and further cervical stump cancer screening is mandatory.